Competency-based medical education for Indian undergraduates: Where do we stand? - Mamta Gehlawat; Goutham Thumati; Priyanka Samala; Chaganti Lalitha Alekhya; Are Shailaja; Anamika Sharma (Wolters Kluwer Medknow Publications, 2024)
The traditional system of medical education was a structure and process-based system with limited assessment of application of knowledge, skills, and attitudes. Decades after the World Health Organization gave preliminary guidelines on Competency-based medical education (CBME) in 1978, countries around the world are still taking to the newer medical education systems. In India, CBME replaced traditional system of medical education in 2019 while the National Medical Council replaced Medical Council of India in 2020. The annual intake of medical undergraduates has reached an all-time high of one lakh students per year in India and our medical education system is taking baby steps toward CBME. The implementation of CBME poses different hurdles for medical educators as well as medical students. Medical educators are yet to develop confidence in the newer teaching learning methods (e.g., Small Group Teaching, Role-play, Peer group learning etc.), along with the array of newer assessment methods. There in lies an immense and urgent need of training medical educators with continued hand holding along with adapting newer teaching learning methods to the students of generation Z who are tech-savvy but anxious and indulged yet stressed. This review has tried to articulate the current situation of CBME in the world and in India, acceptance of CBME by faculty and students and the way forward for India's medical education system.